A Case of Arrowroot Starch Adulteration: Importance of Independent Testing of Dietary Supplements in Clinical Nutrition Research. (7th June 2021) - Sheehab, Asia; Rasmussen, Helen; Ceglia, Lisa
Abstract: Objectives: Adulteration of dietary supplements is widespread and can affect the quality and credibility of clinical nutrition research. In this case report, we describe the difficulties encountered with identity testing of one of our dietary supplements – arrowroot starch – chosen as the placebo for our nutrition intervention trial. Methods: To test the effect of protein and alkali on skeletal muscle health, we planned a randomized controlled trial using a high protein diet supplement with or without an alkaline salt supplement. The study selected Maranta arundinacea L. (arrowroot) starch as placebo because of its neutral potential renal acid load compared to some other starches. Commercially available samples of arrowroot starch were purchased from three different US distributors. Independent identity testing was conducted by digital microscopy by Alkemist Labs (Garden Grove, CA). Results: All three commercially available arrowroot starch samples came with an authentication certificate stating that the starch was derived from the Maranta arundinacea L. plant. On gross examination, the appearance, odor, and consistency of all three samples was similar. On microscopy with digital photo documentation, starch granules from the Maranta arundinacea L. plant range in shape from ovoid, pear-shaped to triangular. The expected size would be 40–75 um and the distinct pattern would have concentric striations and a hilum that resembles a bird or "M". Surprisingly, we found that only one of the three commercially available arrowroot starch samples was characteristic of Maranta arundinacea L. granules on microscopy. The starch granules from samples from the other two US distributors could not be identified. Conclusions: This case study reveals the extensive adulteration of commercially available arrowroot starch in the US. It also highlights the importance of third-party, independent testing of dietary supplements to confirm authentication of the product composition especially for clinical nutrition trials. Funding Sources: NIA R01AG055443–03 (Ceglia).